9=3x-2(3x-9)=x=

Simple and best practice solution for 9=3x-2(3x-9)=x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3x-2(3x-9)=x= equation:



9=3x-2(3x-9)=x=
We move all terms to the left:
9-(3x-2(3x-9))=0
We calculate terms in parentheses: -(3x-2(3x-9)), so:
3x-2(3x-9)
We multiply parentheses
3x-6x+18
We add all the numbers together, and all the variables
-3x+18
Back to the equation:
-(-3x+18)
We get rid of parentheses
3x-18+9=0
We add all the numbers together, and all the variables
3x-9=0
We move all terms containing x to the left, all other terms to the right
3x=9
x=9/3
x=3

See similar equations:

| (-z+28)+(-3z+58)=-4z+79 | | 96=84-12x | | 9z-51=4z-9 | | -3z+9=6z | | 242=7x+16 | | 9x-6=8+7x | | -20+c=-7c+20 | | 118+(3x+1)+x=180 | | 3x-4=2x-2x+1 | | 3/7​=h/14-2/7 | | -8j+3=-7j | | 24-6n=54-24 | | 10x-12=8x-6 | | 4+2x=4(5-x)=x= | | 3=s+4/2 | | 4y=3y+3 | | -3x+5=÷0 | | 16=5+n | | 9q=8q-8 | | 5b=7+6b | | -6h+10-6h=-8-10h | | 7-6v=-41 | | -4t=-5t+4 | | 3x=-6-3(2x+4)=x= | | 87=13+p | | -4(x-13)=8 | | h+6=2h | | 1-3j=-j-j-7 | | 2x+3(x-7)=4=x= | | 1=z-8/2 | | -2=6t-4 | | -10-(-2)=2x-4(x+2)+2x |

Equations solver categories